PENGARUH PENEMPATAN DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. JELAJAH LAUT NUSANTARA JAKARTA - M. Kausar Maulana (Jurnal Ekonomi dan Industri, 2019)
Achievement in work is one of the needs that everyone wants to achieve at work. One of the factors that can affect one's work performance in achieving work targets by placing the right employees in accordance with the abilities and skills possessed and support from the work environment around the employees. This study aims to analyze the presence or absence of influence both simultaneously and partially placement and work environment on employee performance at PT. Archipelago Sea Exploration Jakarta involving 100 respondents. The results of the study indicate that there are influences both simultaneously and partially in the placement and work environment of the work performance of employees at PT. Nusantara Sea Cruising Jakarta.